MULTIGROUP ANALYSIS (MGA): PERAN GENDER PADA KUALITAS AUDIT MELALUI ANALISIS VARIABEL KOMPETENSI DAN INDEPENDENSI AUDITOR - I Made Purba Astakoni; Ni Putu Nursiani; Ni Made Satya Utami; I Ketut Setia Sapta (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2020)
This study has several objectives: 1) to find out and analyze the effect of auditor competence on audit quality, 2) to know and analyze the effect of auditor independence on audit quality, 3) to know and analyze the role of gender as a moderating effect on the influence of auditor competence on audit quality, 4) to find out and analyze the role of gender as a moderating effect on auditor independence on audit quality. This research was conducted at several Public Accounting Firms (KAP) in Denpasar City with the research subjects being all auditors. The populations in this study were all auditors in the city of Denpasar, amounting to 112 people. Determination of the sample is done by purposive method, so that the numbers of samples selected are 53 auditors. Data collection techniques used were interviews with questionnaires with multiple choices closed. In this study data analysis uses the Partial Least Square (PLS) approach. The results showed that the overall strength of the model was stated to be very good. Hypothesis 1, which states that auditor competence has a significant positive effect on audit quality, can be accepted, Hypothesis 2, which states that auditor independence has a significant positive effect on audit quality, can be accepted. Through multi-group analysis it is stated that gender is able to be a moderating variable on the effect of auditor competence on quality an audit. Whereas gender testing as a moderating variable on the effect of auditor independence on audit quality has not been tested.